An explanation for origin unwinding in eukaryotes - Langston, Lance D; O'Donnell, Michael E (eLife, 2019)
Twin CMG complexes are assembled head-to-head around duplex DNA at eukaryotic origins of replication. Mcm10 activates CMGs to form helicases that encircle single-strand (ss) DNA and initiate bidirectional forks. How the CMGs melt duplex DNA while encircling it is unknown. Here we show that S. cerevisiae CMG tracks with force while encircling double-stranded (ds) DNA and that in the presence of Mcm10 the CMG melts long blocks of dsDNA while it encircles dsDNA. We demonstrate that CMG tracks mainly on the 3’−5’ strand during duplex translocation, predicting that head-to-head CMGs at an origin exert force on opposite strands. Accordingly, we show that CMGs that encircle double strand DNA in a head-to-head orientation melt the duplex in an Mcm10-dependent reaction.
Keywords: helicase; replication origin; DNA replication